Health-care reform implementation challenges at suburban areas in Isfahan province: A qualitative study - Nasrin Shaarbafchizadeh; Zahra Fouladi; Pejman Aqdak; Ahmad Reza Raeisi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Health system reform plan in public health sector in Iran in the first phase focused on improving primary health care in suburban areas in and around big cities. The present study was conducted to assess the implementation process challenges of the reform plan in comprehensive health service centers at suburban areas of Isfahan in 2019. MATERIALS AND METHODS: This qualitative study with conventional content analysis approach was conducted in 2019. Participants were purposefully selected and interviewed at provincial levels from Isfahan University of Medical Sciences health department and health-care providers of comprehensive health services centers. The saturation point was reached after 21 face-to-face semi-structured interviews. Thematic analysis was employed to analyze transcribed documents assisted by MAXQDA version 10. RESULTS: The results revealed four main themes; the human resource management, the executive management, the electronic infrastructure, and the resource management.The major challenges in the implementation planning process included: the referral system, monitoring and supervision, electronic services infrastructure in the design and development of the EHR called the SIB system, lack of instructions guide, salaries and benefits, inconsistent financial and human resources and inappropriate allocation of theses resources. CONCLUSION: Despite the achievements in the development of the Iran health system reform plan, there were many challenges in the implementation planning process. It is recommended that theses challenges be reviewed and amended by health system managers and policymakers.